Penerapan Teknologi Quick Response Code dan First in First out Berbasis Web Pada Sistem Pemesanan - Rosella, Rosella; Priandika, Adhie Thyo; Puspaningrum, Ajeng Savitri (PT. SNN MEDIA TECH PRESS, 2024)
Problems that occur from the order side are errors in recording or taking customer orders. This can result in incorrect order delivery or customers who are dissatisfied with the service. If the booking system is inefficient, the booking may take too long to process. The implementation of ordering and payment systems using Quick Response Code (QR Code) technology and First in First Out (FIFO) methods has delivered significant results in improving operational efficiency and customer experience. The use of QR Codes allows customers to easily scan codes on menus or products they order using their mobile devices. This reduces the time it takes to order food or products and avoids human error in ordering. Based on the results of the recapitulation of the 6 test criteria that have been carried out, the results of the number of answers from respondents are obtained which have a value of 100% in accordance with testing system functionality using blackbox testing. The results of processing respondent response data based on ISO 25010 aspects of Performance Efficiency, Operability Aspects, and Functional Efficiency Aspects obtained a total score of 85.47%. Based on this, the ISO 25010 prototype is very good for ordering systems using Web-Based Quick Response Code (QR Code) and First in First out (FIFO) Technology.